1986
DOI: 10.2466/pr0.1986.59.2.1015
|View full text |Cite
|
Sign up to set email alerts
|

Personality Correlates of a Test of Honesty

Abstract: The goal of this study is to assess the construct validity of a preemployment test of honesty, the Phase II Profile, in relation to the personality traits measured by the Sixteen Personality Factor Questionnaire. Of the four predetermined criteria, only the relationship to emotional stability was significant. Two of the 12 relationships expected to be nonsignificant were significant. The correlations obtained in this study and in two others were so low that the construct validity for the tests of honesty in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Harris (1984) reported similar patterns of correlations with the 16PF for the London House PSI and for the Reid Report. Logan, Koettel, and Moore (1986) reported correlations with the 16PF for the Phase I1 profile for a sample of college students; the profiles of correlations was quite different from that found with the London House PSI and the Reid Report (correlations between profiles of .28 and .30, respectively, whereas the London House-16PF profile and the Reid Report-l6PF profile correlated .88). Logan et al question whether the differences in profiles are the result of differences between the tests or differences in situations (e.g., applying for a job vs. anonymous participation in a research project).…”
Section: Relationshqs With Other Constructsmentioning
confidence: 71%
“…Harris (1984) reported similar patterns of correlations with the 16PF for the London House PSI and for the Reid Report. Logan, Koettel, and Moore (1986) reported correlations with the 16PF for the Phase I1 profile for a sample of college students; the profiles of correlations was quite different from that found with the London House PSI and the Reid Report (correlations between profiles of .28 and .30, respectively, whereas the London House-16PF profile and the Reid Report-l6PF profile correlated .88). Logan et al question whether the differences in profiles are the result of differences between the tests or differences in situations (e.g., applying for a job vs. anonymous participation in a research project).…”
Section: Relationshqs With Other Constructsmentioning
confidence: 71%
“…The task was based on previously published work (26,27). On all trials, a white fixation cross appeared for 500 ms; it was replaced by an "X" or "O" "go-signal" for 1000 ms (Fig.1).…”
Section: Behavioral Taskmentioning
confidence: 99%
“…Results of research with the Personnel Reaction Blank (Gough, 1971), the Employee Reliability Index (J. Hogan & R. Hogan, 1989Hogan, , 1992, and the Employment Inventory (Personnel Decisions, Inc., 1985) point to the psychological meaning of personality-based integrity measures. For example, Ones (1993) concluded that such tests reflect the Big Five theme of conscientiousness and, to a lesser degree, emotional stability and agreeableness (see also Logan, Koettel, & Moore, 1986; Murphy & Lee, 1994). However, the psychological meaning of overt integrity tests is unclear; thus, Woolley and Hakstian (1992) found that the relationship between overt and personality-based integrity measures varied.…”
mentioning
confidence: 99%